CASE STUDY: APPLICATION OF ENDORPHINE MASSAGE IN REDUCING BACK PAIN SCALE IN THIRD TRIMESTER PREGNANT WOMEN - Fajrin, Dessy Hidayati; Theresia Lorensha Simbolon (Rena Cipta Mandiri, 2024)
Pregnancy is a meaningful experience with all the changes, both physical and psychological. One of the uncomfortable changes that occur in the third trimester is lower back pain. Low back pain can have a negative impact on the quality of life of pregnant women because it interferes with daily physical activities. In addition, back pain in pregnant women also has an impact on reducing the quality of sleep of the mother which can reduce the quality of life of the mother and fetus. This study used qualitative research methods in the form of case studies by providing Holistic Pregnancy Physiological Midwifery Care. The research subjects were pregnant women Mrs. D, 31 years old GIIIPIIA0, 37 weeks pregnant with lower back pain. The results showed that at the 37th week of pregnancy visit the respondent stated that back pain in cirrhosis pain showed a number of 6. After Endorphine massage the results of the pain scale became 4. This shows that giving Endorphine massage can reduce complaints of back pain in third trimester pregnant women.